Bilateral Cavernous Carotid Aneurysms: Atypical Presentation of a Rare Cause of Mass Effect. A Case Report and a Review of the Literature - Gagliardi, Delia; Faravelli, Irene; Villa, Luisa; Pero, Guglielmo; Cinnante, Claudia; Brusa, Roberta; Mauri, Eleonora; Tresoldi, Laura; Magri, Francesca; Govoni, Alessandra; Bresolin, Nereo; Comi, Giacomo P.; et al. (Frontiers in Neurology, 2018)
Bilateral cavernous carotid aneurysms (CCAs) represent a rare medical condition that can mimic other disorders. We present a rare case of bilateral CCAs simulating an ocular myasthenia. A 76-year-old woman presented with a history of fluctuating bilateral diplopia and unilateral ptosis, which led to the suspicion of ocular myasthenia. Magnetic resonance imaging (MRI) and magnetic resonance angiography (MRA) of the brain showed the presence of large bilateral aneurysms of the carotid cavernous tract. After an unsuccessful attempt with steroid therapy, the patient underwent endovascular treatment, with mild improvement. Bilateral CCAs can cause pupil sparing third nerve palsies and other cranial neuropathies that may mimic signs and symptoms of disorders of the neuromuscular junction. Therefore, the possibility of a vascular lesion simulating ocular myasthenia should be considered especially in older patients.